2020
DOI: 10.3390/cells9040991
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Derived Extracellular Vesicles for Tissue Engineering and Regenerative Medicine Applications

Abstract: Mesenchymal stem cells (MSCs) are being extensively investigated for their potential in tissue engineering and regenerative medicine. However, recent evidence suggests that the beneficial effects of MSCs may be manifest by their released extracellular vesicles (EVs); typically not requiring the administration of MSCs. This evidence, predominantly from pre-clinical in vitro and in vivo studies, suggests that MSC-EVs may exhibit substantial therapeutic properties in many pathophysiological conditions, potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
172
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(173 citation statements)
references
References 167 publications
(167 reference statements)
0
172
0
1
Order By: Relevance
“…With increasing knowledge, it became evident that some of the regulatory activities relate to soluble factors and thus are found in MSC-CM and EV [14]. EV anti-apoptotic, angiogenic and regenerative potentials have made them rise as a potential alternative cell-free therapeutic prospect circumventing many of the safety challenges regarded in cell therapy [15]. EV, small vesicles secreted by a variety of cell types, are known to take part in cell-cell communication [16].…”
Section: Introductionmentioning
confidence: 99%
“…With increasing knowledge, it became evident that some of the regulatory activities relate to soluble factors and thus are found in MSC-CM and EV [14]. EV anti-apoptotic, angiogenic and regenerative potentials have made them rise as a potential alternative cell-free therapeutic prospect circumventing many of the safety challenges regarded in cell therapy [15]. EV, small vesicles secreted by a variety of cell types, are known to take part in cell-cell communication [16].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies suggest that EVs isolated from the cell secretome might also be efficient for the treatment of COVID-19 [20]. MSC-derived EVs were shown to produce similar effects as their parent cells; and they can be safely stored for long periods without losing function and have shown similar or better results than MSCs in animal models [19].…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19) will have a long-lasting impact on the biopharmaceutical industry. In particular, the urgent need both for a preventive vaccine and for advanced therapeutics will stimulate the growth of the post-COVID-19 bioindustry in ways that were unthinkable before.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, BMSCs have many advantages, such as extensive sources, easy to culture in vitro, and less ethical issues, so the study of BMSCs is more extensive at present. Researchers have reported that MSCs can exert beneficial effects by their released extracellular vesicles, however, whether ENaC is involved in the above process is still rarely known [30]. It has been confirmed that patients with ALI have disorders of pulmonary fluid clearance, and evidence has also shown that reabsorption of Na + by ENaC is an important step to maintain the balance of alveolar fluid [31].…”
Section: Discussionmentioning
confidence: 99%